Dilated Cardiomyopathy Induced by Chronic Starvation and Selenium Deficiency - Soham Dasgupta; Ashraf M. Aly (Hindawi Limited, 2016)
Protein energy malnutrition (PEM) has been rarely documented as a cause of cardiovascular abnormalities, including dilated cardiomyopathy. Selenium is responsible for antioxidant defense mechanisms in cardiomyocytes, and its deficiency in the setting of PEM and disease related malnutrition (DRM) may lead to exacerbation of the dilated cardiomyopathy. We report a rare case of a fourteen-year-old boy who presented with symptoms of congestive heart failure due to DRM and PEM (secondary to chronic starvation) along with severe selenium deficiency. An initial echocardiogram showed severely depressed systolic function consistent with dilated cardiomyopathy. Aggressive nutritional support and replacement of selenium and congestive heart failure medications that included diuretics and ACE inhibitors with the addition of carvedilol led to normalization of the cardiac function within four weeks. He continues to have significant weight gain and is currently completely asymptomatic from a cardiovascular standpoint.